Fetal humerus length as a Gestational Age parameter – A nomogram for local Indian population. - Singh, Avantika; Kr. Anand, Arvind; Ranjan, Megha (Journal of Neonatal Surgery, 2025)
Background: Precise understanding of the fetus's gestational age is necessary to achieve a logical and accurate conclusion. Gestational age can be accurately predicted by biparietal diameter, head circumference, abdomen circumference, and femur length. The current study was conducted to estimate fetal gestational age by measuring humerus length between 18 and 36 weeks period of gestation of normal singleton pregnancies and to compare humerus length with conventional measurements as an additional tool to improve accuracy because the humerus is not commonly employed as a biometric parameter for calculating the GA. Materials and methods: In this cross-sectional study conducted in Department of Radiology, SMS&R, Sharda Hospital, Greater Noida, Uttar Pradesh, India, 150 women between the gestational ages of 18 and 36 weeks gestation who had a viable singleton pregnancy and a low miscarriage risk were included. Using electronic calipers on ultrasonography, fetal measurements were taken which include femur length, humerus length, head circumference, abdomen circumference and biparietal diameter. The gestational age obtained from the four conventional parameters was confirmed with the gestational age obtained from date of last menstrual period to maintain standard and to rule out any growth restriction which would affect the nomogram. Statistics were used to analyze the data. Results: The average humerus length in this study was 26.63±0.67 mm at 18 weeks and 48.51±0.59 mm at 28 weeks. Univariate linear regression was used to find out relationship of HL and gestation age by LMP and shows a strongly significant linear relationship between humerus length and gestational age. The present study revealed coefficient of correlation of humerus length with gestational age of r = 0.994 demonstrating a strong linear association. Conclusion: In this study, the measurement of the fetal humerus length was used to develop a nomogram for the local Indian population between 18 to 36 week of gestation.